Study on Continuous Catalyst Reformer and Catalyst Regeneration Process - Subramaniam, Nagentheran (Universiti Teknologi PETRONAS, 2009)
Regeneration of coked catalyst in a naphtha reformer is studied based on the effectiveness of rate coke bum off. Catalyst is temporarily deactivated by the coke deposits which are burnt in the regeneration for the catalyst reactivation. Catalyst gets deactivated by coke deposition blocking the active sites and reduces the selectivity of catalyst and the products yields. For predicting the behavior subject to catalyst deactivation, coking rate equation and the kinetic model is obtained. All reformers are moving bed and radial flow reactors. The coked catalyst are moved continuously and slowly from the reactors, withdrawn from the last reactor regenerated in a regeneration section and returned to first reactor as fresh catalyst. Coke content on the catalyst increases with residence time of catalyst. Catalyst deactivation is directly proportional to the amount of coke deposits on the catalyst. To understand and contribute to this problem, a modeling of the regeneration of coked catalyst particles (Pt-Al203) are used as model catalyst to (I) determine of the intrinsic and effective kinetics of coke bum-off (2) characterization of the catalyst's on influence of the temperature on the pore effectiveness factor, rate of mass transfer, and reactivity of coked catalyst (3) Influence ofcarbonload on porosity and tortuosity of the catalyst. With this information, modeling of the coked catalyst regeneration is produced.